ANALISIS STABILITAS HASIL GENOTIPE JAGUNG MENGGUNAKAN METODE FIXED AMMI - LOLITA, MODANA; SUKARSA, I KOMANG GDE; SUSILAWATI, MADE (E-Jurnal Matematika, 2019)
Additive Main Effect and Multiplicative Interaction (AMMI) is a method that is used in research to study interaction between genotype and location. The aim of this research is to apply fixed AMMI in examining the production of corn genotype data and to explore yield stability of its based on biplot picture and AMMI Stability Value (ASV). This research uses six corn genotypes, eight trial locations, and three repetitions. The Interaction Principal Component Analysis (IPCA) that are significant to entered in the model based on analysis of variance fixed AMMI are IPCA 1 , IPCA 2 , and IPCA 3 with total diversity interaction as much as 92,16%. The biplot picture and ASV should the stable genotype in all location are genotype KUI Carotenoid Syn FS. 17-3-2-B-B  T01 and genotype CML 305-B-B  T01 . In addition, corns that are able to adapt only in certain location is: genotype KUI Carotenoid Syn FS. 5-1-5-B-B  T01, genotype KUI Carotenoid Syn FS. 25-3-2-B-B  T01, genotype KUI Carotenoid Syn FS. 17-3-1-B  T01, and genotype CML 130-B-B  T01.